Effectiveness of recovery actions on deviant customer behavior — the moderating role of gender. - Boo, Huey Chern; Matilla, Anna S.; Tan, Ching Yeng (Elsevier, 2013)
This paper aims to examine how gender interacts with various recovery actions on perceived employee effort, complaint handling satisfaction, and behavioral intention in the case of deviant customer behavior in an East-Asian context. Study 1, a qualitative study, reveals that consumers expect companies to take appropriate remedial actions when a service consumption experience is affected by deviant customer behaviors (e.g., smoking in non designated area). Study 2 employed a 2 (gender) × 6(recovery actions) between subject design in a restaurant setting. Results show that confronting the deviant customer received the highest customer ratings in terms of perceived employee effort, complaint handling satisfaction, and behavioral intention. However, gender moderated the relative effectiveness of recovery actions. Relocating the focal customer was equally good as compensation for women while men were less appreciative of relocation than compensation. In sum, service providers are advised to initiate some form of recovery action in response to deviant customer behaviors.